Zakat Sebagai Variabel Intervening dalam Mempengaruhi Pertumbuhan Ekonomi di Indonesia - Wahyu Nita Kurrotaa'yun Nuriski (ITB AAS INDONESIA Surakarta, 2023)
Indonesia's economic growth has fluctuated based on the size of the Gross Domestic Product (GDP). This study discusses consumption and investment factors as economic growth factors departing from the equation Y = C + I by adding zakat as an intermediary factor based on the large potential of zakat in Indonesia. This study aims to: (1) examine the effect of consumption on economic growth in Indonesia, (2) examine the effect of investment on economic growth in Indonesia, (3) examine the effect of zakat on economic growth in Indonesia, (4) examine the effect of consumption on economic growth through zakat, (5) examine the effect of investment on economic growth through zakat. The research method uses a quantitative approach, secondary research data with a saturated sample of 44 samples, namely quarterly data on economic growth, consumption, investment, and zakat distribution from quarter I-2011 to quarter IV-2021. The research results show implications for Zakat managers and the Government to be able to synergize together to optimize zakat management to be able to intervene and accelerate the rate of economic growth. Keywords: Consumption, Investment, Economic Growth, Zakat